2016
DOI: 10.1007/s00429-016-1243-8
|View full text |Cite
|
Sign up to set email alerts
|

Human navigation network: the intrinsic functional organization and behavioral relevance

Abstract: Spatial navigation is a crucial ability for living. Previous work has revealed multiple distributed brain regions associated with human navigation. However, little is known about how these regions work together as a network (referred to as navigation network) to support flexible navigation. In a novel protocol, we combined neuroimaging meta-analysis, and functional connectivity and behavioral data from the same subjects. Briefly, we first constructed the navigation network for each participant, by combining a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 101 publications
(152 reference statements)
3
31
0
1
Order By: Relevance
“…To compare to language-related networks, we also analyzed three other functional cortical networks: the spatial navigation network (SNN), fronto-parietal multiple demand network (MDN, similar to the dorsal attention network (Yeo et al, 2011)), and default mode network (DMN). The sets of cortical regions defined for these networks (see Methods) appeared consistent with previous literature (Buckner, Andrews-Hanna, & Schacter, 2008;Crittenden, Mitchell, & Duncan, 2016;Kong, Wang, et al, 2017) and showed little overlap with the sentence processing networks defined above (Fig. 2).…”
Section: Functional Networksupporting
confidence: 78%
See 3 more Smart Citations
“…To compare to language-related networks, we also analyzed three other functional cortical networks: the spatial navigation network (SNN), fronto-parietal multiple demand network (MDN, similar to the dorsal attention network (Yeo et al, 2011)), and default mode network (DMN). The sets of cortical regions defined for these networks (see Methods) appeared consistent with previous literature (Buckner, Andrews-Hanna, & Schacter, 2008;Crittenden, Mitchell, & Duncan, 2016;Kong, Wang, et al, 2017) and showed little overlap with the sentence processing networks defined above (Fig. 2).…”
Section: Functional Networksupporting
confidence: 78%
“…It uses text-mining techniques to detect frequently used terms as proxies for concepts of interest in the neuroimaging literature: terms that occur at a high frequency in a given study are associated with all activation coordinates in that publication, allowing for automated term-based metaanalysis. Despite the automaticity and potentially high noise resulting from the large-scale meta-analysis, this approach has been shown to be robust and meaningful (e.g., Helfinstein et al, 2014;Kong, Song, et al, 2017;Kong, Wang, et al, 2017;Yarkoni et al, 2011), due to the high number of studies included. We used database version 0.6 (current as of July 2018) which included 413,429 activation peaks reported in 11,406 studies (see below for the search terms employed).…”
Section: Bilandginmentioning
confidence: 99%
See 2 more Smart Citations
“…Arnold, Burles, Bray, Levy, and Iaria () examined this in the context of visual path integration and found that individuals with stronger interactions among frontal and parietal areas performed more accurately. More recently, stronger interaction between right posterior hippocampus and right retrosplenial cortex at rest (Sulpizio, Boccia, Guariglia, & Galati, ) and greater betweenness centrality of right retrosplenial cortex within a network of regions involved in navigation tasks (Kong et al, ) at rest were found to be associated with better self‐reported navigation ability. These studies show that task‐related communication between brain regions, as well as their interactions at rest, hold information about the variation in spatial navigation ability between individuals.…”
Section: Introductionmentioning
confidence: 99%